Analisis dalam Novel L’Etranger: (The Outsider) Karya Albert Camus - Salsabila, Hanum (Maliki Interdisciplinary Journal, 2024)
The novel L’Etranger (The Outsider) by Albert Camus tells the story of Meursault, an apathetic young man who is sentenced to death for killing an Arab on the coast of Algeria. This novel explores the themes of existentialism, the absurdity of life, and the consequences of ignoring social norms. Meursault is depicted as an individual who is indifferent and not bound by social norms. He showed no emotion when his mother died, had no meaningful relationships with others, and no sense of purpose in life. He lives his life without meaning or purpose, only following his own impulses and desires. ‎This novel ends with Meursault’s reflection on the absurdity of life. He realized that there was no meaning or purpose attached to life, and that he would die without having made a difference in the world. However, he found peace in the acceptance of this absurdity and ‎chose to die with courage and dignity.‎